2014
DOI: 10.1042/bj20140400
|View full text |Cite
|
Sign up to set email alerts
|

Controlling gene networks and cell fate with precision-targeted DNA-binding proteins and small-molecule-based genome readers

Abstract: Transcription factors control the fate of a cell by regulating the expression of genes and regulatory networks. Recent successes in inducing pluripotency in terminally differentiated cells as well as directing differentiation with natural transcription factors has lent credence to the efforts that aim to direct cell fate with rationally designed transcription factors. Because DNA-binding factors are modular in design, they can be engineered to target specific genomic sequences and perform pre-programmed regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 252 publications
(299 reference statements)
0
10
0
Order By: Relevance
“…Such "pioneer" factors facilitate binding by other transcription factors and are usually necessary for the maintenance of cell identity. The forced overexpression of pioneer factors is often sufficient for cell-fate conversion (26). Our data suggest that polyamides, by virtue of being able to access repressive heterochromatin, could be harnessed to serve as pioneer factors, but the conditions under which they might do so will guide the next phase of polyamide design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such "pioneer" factors facilitate binding by other transcription factors and are usually necessary for the maintenance of cell identity. The forced overexpression of pioneer factors is often sufficient for cell-fate conversion (26). Our data suggest that polyamides, by virtue of being able to access repressive heterochromatin, could be harnessed to serve as pioneer factors, but the conditions under which they might do so will guide the next phase of polyamide design.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed chromatin accessibility is a major barrier to binding by naturally occurring DNA-binding proteins as well as artificial DNA binders, such as zinc fingers, transcription activator-like effectors, and the RNA-guided CRISPR-Cas9 (26,27). Elegant biophysical and biochemical studies have demonstrated that polyamides bind to solvent-exposed cognate sites on nucleosomes without significant loss in affinity or specificity (28,29).…”
mentioning
confidence: 99%
“…The majority of such challenges can be circumvented by artificial transcription factors (ATFs) that directly target key gene regulatory networks that govern cell fate changes(Fig. A) . Importantly, libraries of ATFs can also be used to screen thousands of genes in parallel to produce a phenotype of interest without prior knowledge of relevant natural TFs or gene regulatory networks .…”
Section: Natural Artificial and Synthetic Transcription Factors In mentioning
confidence: 99%
“…On the other hand, the origin of the cell type can also influence the immune properties of iPSCs, possibly due to differences in reprogramming memory (Polo et al, 2010). The difference in transcription and epigenetic landscape between ESCs and iPSCs is that the latter type bearing some memory of their original differentiated state (Eguchi et al, 2014). The memory of iPSCs can result in the partial retention of the transcriptional and epigenetic features of the source cells.…”
Section: The Current State Of Ipscs Andmentioning
confidence: 99%